AN EMPIRICAL STUDY OF KEY FACTORS TO EFFECTIVELY OPERATE STRATEGIC PERFORMANCE MANAGEMENT SYSTEM - Stříteská, Michaela; Zapletal, David; Jelínková, Lucie (My University, 2018)
Measuring performance is a fundamental aspect of successful management systems, which are focused on implementing strategy and maintaining competitive advantage. Effective performance measurement must be founded on systematic and comprehensive research on company activities and results in order to constantly develop key competencies. This paper is comprised of a number of sections that tie into each other thematically. First, an effective strategic performance management system and factors that influence its implementation are defined from a theoretical perspective. Then, the methodology and research methods used in the paper are described. The next step for the companies being investigated was to identify their strategic performance management system’s development level according to whether it encompasses characteristics indicated in the literature and whether a number of key factors are demonstrably managed. Only then does the paper proceed to investigate the relationship between the strategic performance management system’s level of development and both the length of time it has been implemented as well as key factors that are currently managed.
Empirická studie klíčových faktorů pro efektivní fungování strategického systému řízení výkonnosti
Keywords: performance measurement; performance management; system; strategy; effectiveness; měření výkonnosti; řízení výkonnosti; systém, strategie; efektivnost